Etiología de prurigo atópico en niños detectado, por prick-test. Centro de Asma y Alergias. Riobamba, 2018 - Llagua Canchiña, Martha Elizabeth (2019)
Introduction: Atopic dermatitis is the dermal manifestation of atopy, it is defined as the tendency to overreact to multiple substances and can manifest itself as different diseases. This prurigo often becomes chronic, resistant to the usual treatment with severe deterioration of the quality of life. It is linked to a delayed type hypersensitivity to mites either by direct contact or by inhalation. Method: A descriptive, cross-sectional, retrospective study was carried out, the universe was made up of 89 pediatric patients, treated in an outpatient clinic of Centro Asma and Allergias Muñoz in the 2018 period. The Prick-Test was used to identify the sensitivity to certain types of allergens that caused prurigo. Results: it was found that there is a prevalence in children 2 years of age corresponding to (29.2%) and 3 years with (24.7%), predominantly the male sex with a total of 55 cases (61.8%) of the sample under study On the other hand, it is important to indicate that the most frequent allergens were those belonging to the fungal group (Hormodendron with 53 cases (59.55%), followed by Alternaria and Aspergillus with 51 cases each (57.30%)), As for the diseases associated with prurigo, the syndrome of hyperreactivity of the airways stands out with 21 cases, representing (23.60%), allergic rhinitis with 15 cases being (16.85%), finally the treatment based on immunotherapy specific received 89 patients corresponding to (100%).